Simulação por dinâmica molecular de um trímero de poliuretano em solventes orgânicos e em água - Ambrozio, Stêner Romanel (2018)
Polymer is a macromolecule composed of many (tens of thousands) of repeating units called meros, attached by covalent bond. Polyurethane (PU) is formed by organic units of isocyanates and alcohols. The high production demand requires means of recycling this polymer. The study of the interaction of polyurethane molecules with solvents is of academic interest since this study may contribute to new processes involving polyurethane. D-limonene is a chemically green organic solvent, and studying it as a solvent alternative and comparing it with other solvents is relevant. Computational methods are a good alternative for the study of diverse properties of materials, since they allow to construct and investigate at the molecular level. In addition, they can be used prior to conducting experiments in the laboratory, or after the experiments, seeking to confirm and / or elucidate the results found. A methodology widely employed in the study of diverse systems is the Molecular Dynamics (DM), which makes it possible to study interactions at the atomic level. The objective of this work was to simulate the Molecular Dynamics of a polyurethane trimer based on MDI and Ethylene Glycol in d-limonene, water, benzene and toluene, and to compare the results. The results of spinning radius and RMSD showed that the TPU molecule presents a significant conformation change in the solvents studied, mainly in toluene. This can be explained by the fact that the TPU molecule presents polar and nonpolar sites, causing a great amount of attractions and repulsions in the solvents. In addition, the TPU molecule does not have considerable size, so its center of mass can be moved with some ease. The energy analyzes show that in system 1 the interactions of the TPU molecule with water are more favorable than in other organic solvents. In organic solvents the TPU molecule behaves similarly. The d-limonene can be indicated as solvent used in reactive media containing polyurethane molecules, because the TPU molecule has properties similar to those presented in benzene and toluene. In addition, d-limonene has the advantage of being a chemically green solvent and having a higher boiling point than other solvents, allowing higher temperatures to be achieved in reaction processes.